Fully degradable PLA-based composite reinforced with 2D-braided Mg wires for orthopedic implants. (12th April 2017) - Li, Xuan; Chu, Chenglin; Zhou, Li; Bai, Jing; Guo, Chao; Xue, Feng; Lin, Pinghua; Chu, Paul K.
Abstract: Fully degradable poly-lactic acid (PLA) is reinforced with 2D-braided magnesium alloy wires (Mg wires or MAWs) for bone fixation devices. The relationship between the mechanical/degradation properties of the composite and microstructural features such as braiding angle, volume fraction, and interface properties is investigated. The biaxial mechanical properties of the composite can be tailored by the microstructure. When the braiding angle is 45°, the composite has the highest shear and impact strength and increasing the volume fraction simultaneously improves the tensile, bending, shear, and impact strength. Results obtained by the finite element method show that the screw hole undermines the safety factor of the composite under micro-strain. Acidic degradation of pure PLA can be mitigated by the corporation of MAWs and a degradation model is proposed to predict the mechanical properties of the composite during immersion. Our results reveal a relationship between the bending strength, molecular weight, and immersion time.